Cross-Regional Jurisdiction Challenges of the E-Court System Due to Infrastructure Limitations and Their Impact on Civil Justice Access in Remote Areas - Panca Hastomo; Rizal Santosa; Alindra Dwi; Ryan Shoim; Agung Pangestu; Sabta Tri; Aurelia Intan; Syifa Rana Tsary (Asosiasi Dosen Muda Indonesia, 2026)
The transformation of legal services through the implementation of the E-Court system is part of judicial modernization aimed at realizing effective and inclusive access to justice. This study seeks to analyze the regulation of cross-regional jurisdiction under Supreme Court Regulation (PERMA) Number 1 of 2019 and to examine the challenges of digital infrastructure in providing access to justice for civil litigants in remote areas. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that PERMA Number 1 of 2019 enables the implementation of e-summons and electronic hearings without eliminating the court’s authority based on territorial jurisdiction. However, its effectiveness still depends on the consent of the parties and technical readiness. On the other hand, limitations in internet connectivity, technological devices, and digital literacy in underdeveloped, frontier, and outermost (3T) regions create disparities in access to justice. This study concludes that the transformation of legal services through E-Court requires regulatory strengthening, the development of digital infrastructure, and the implementation of a hybrid service model to ensure that the principles of justice, legal certainty, and utility are equitably realized for all people across Indonesia.